THE CATEGORIZATION OF SOLUTIONS FOR INDIGENOUS PEOPLE IN CUSTOMARY LAND-USE CONFLICTS IN INDONESIA - Daniel Jesayanto Jaya; Retna Hidayah; Diya Ul Akmal; Anjulin Yonathan Kamlasi (SAMPURASUN, 2021)
Human need for land has influenced land use behavior and is an acute problem in many regions. Many areas have changed their original function in order to sustain human life, one of which causes forests to be converted into settlements, plantation and agricultural areas as well as mining areas. However, often the converted land is customary land in the form of forests and not a few that have long been disputed. In the era of independence, the government recognized that customary land belonged to the state. In its implementation, customary land is recognized by the government but its ownership rights are not. The indigenous people are only allowed to manage it. This study aims to categorize solutions that can be used in resolving land-use conflicts over customary lands. This study used the traditional review method with secondary data obtained from appropriate and relevant sources. Customary land is recognized in Indonesian law through UUPA No. 5 of 1960. The highest right to land owned or controlled by community members and its implementation is regulated by customary / village elders called ulayat rights, but provided that its existence and implementation still exist. In cases that occur in various countries, there are various kinds of implementation irregularities caused by excessive usage patterns or not according to the main purpose of their use. In Indonesia, irregularities in the implementation of the Law on indigenous peoples to manage their land are often found. Even some government policies are still detrimental to society. Therefore, in resolving customary land conflicts, one must look at various angles and see the history of disputed land, and can refer to several cases that have occurred in other countries. The categorization of land-use conflict solutions can be viewed from the point of view of the resolution process, the distribution of use of customary land use for indigenous peoples in conflict, what changes in land use have occurred according to procedures or not, mapping is needed to avoid vertical conflicts. and horizontally, and the involvement of the disputing parties, as well as based on ownership rights over customary land.